Quality of Adhesions After Sutured Paramedian vs. Laparoscopic Toggle Abomasopexy in an Ovine Model. Issue 4 (4th April 2016) - Thomas, Keri L.; Wilson, David G.; Bracamonte, José L.; Carmalt, James L.; Luby, Christopher D.
Abstract : Objective: To evaluate adhesions created by abomasopexies using either chromic gut or polydioxanone suture through a right paramedian approach and determine whether a laparoscopic toggle technique is an acceptable alternative to open abomasopexy using an ovine model. Study Design: Experimental study. Animals: Mature ewes (n=30). Methods: Ewes received 1 of 3 abomasopexy techniques (n=10): right paramedian approach using chromic gut or polydioxanone, or a laparoscopic toggle technique. After euthanasia 8 weeks postoperatively, adhesions were removed en bloc and adhesion cross‐sectional area (width × length) and depth (distance from abdominal wall to abomasum) were measured and given a grade of 0–3 based on the quality of adhesion. Surgical time was recorded and compared for each technique. Significance was set at P ≤.05. Results: Abomasopexies performed with either suture material resulted in a significantly larger mean cross‐sectional area and higher adhesion grades compared to those performed using the toggle. Width and length of adhesions formed using chromic gut or polydioxanone were not significantly different; however, both were significantly wider and longer than those formed using the toggle. The laparoscopic toggle technique required significantly less surgical time than the sutured techniques. Conclusion: Polydioxanone is as effective as chromic gut suture material in inducing abomasal adhesion formation in our sheep model. The clinical significance of the size and grade of adhesions formed is unknown and requires further investigation before the laparoscopic toggle technique can be recommended as a replacement for paramedian abomasopexy in cattle for the treatment of displaced abomasum.